Ketidakhadiran tenaga kesehatan di puskesmas: analisis data IFLS 2012 di Wilayah Indonesia Timur - Candra Candra; Lutfan Lazuardi; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat (BKM), 2016)
Absenteeism among primary health center workers: an analysis of the 2012 IFLS in Eastern IndonesiaPurposeThe study aimed to determine the determinants for absence of health centre employees in urban and rural areas in the eastern Indonesian region using data IFLS East 2012.MethodsThis study was a quantitative research using secondary data analysis of Indonesian family life survey (IFLS) East 2012 with health professionals using a cross-sectional design. The population was all health workers in seven provinces in Eastern Indonesia (Nusa Tenggara Timur, East Kalimantan, South East Sulawesi, Maluku, North Maluku, Papua, West Papua). The research sample totaled 1809 health workers. Analysis used STATA version 12.ResultsThe results of bivariable analysis on the variables gender, type of health worker, tenure, health center locations showed a significant relationship with absenteeism the health center employee. The results showed from the multivariable analysis showed higher odds ratio at rural health centers versus urban locations with absenteeism of health center employee, but there was no significant difference.ConclusionThe absenteeism of health center employees is influenced by various multi-factors especially gender, types of health worker, tenure and health center locations. Increased capacity in the management by health center managers, broader authority to enforce discipline, and monitoring by the community is expected to decrease absenteeism of health center employees.